Perovskite cobaltates/p-silicon heterojunction photodiodes - Yalcin, Mesut; Ozmen, Denizhan; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2019)
Sr doped Y1-xSrxCoO3/p-Si photodiodes were fabricated by the drop-casting technique. The electrical and photoresponse properties of Al/p-Si/Y1-xSrxCoO3/Al diodes were investigated by using current-voltage, capacitance-voltage, and transient photocurrent measurements. The calculated average barrier heights and ideality factors are 0.343 eV (x = 0), 0.356 eV (x = 0.01), 0.386 eV (x = 0.05) and 0.393 eV (x = 0.15), 13.43 (x = 0), 17.27 (x = 0.01), 12.71 (x = 0.05) and 15.75 (x = 0.15) for Al/p-Si/Y1-xSrxCoO3/Al diodes at different illumination intensities, respectively. The lowest ideality factor and series resistance were observed from x = 0.05 doped diode. These results suggest that the Al/p-Si/Y1-xSrxCoO3/Al diodes can be used optoelectronic device applications. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Y1-xSrxCoO3; Perovskite cobaltate; Photodiode; Ideality factor; Barrier height